(untitled) (Моделювання, керування та інформаційні технології, 2019)
The process of resonance oscillations of a cantilever-fixed polymer rod with a rectangular cross section is considered. The values of the resonant frequencies of the own oscillations of the rod were obtained. The possibility of determining the real and imaginary parts of a complex dynamic Young’s modulus of a polymeric rod at basic resonance frequency is shown.